Publicsector worker safety and legal remedies - Bernat, Frances P. (American journal of criminal justice, 1994)
While much is known about the affirmative responsibilities private employers must undertake in order to protect workers on the job, the responsibilities of public-sector employers have not been heretofore addressed. This article analyzes federal laws that pertain to worker safety. These laws will be discussed in light of legal responsibilities placed on public-sector agencies to provide a safe work environment for employees.